Adopting the Factors That Motivate and Sustain Teachers Interest in the Teaching Profession for National Development in Education - Ifeakor, Chinedu; Odo, Anselm Ikenna (Jurnal Office, 2020)
This paper sought to adopt the factors that motivate and sustain the teacher’s interest in the teaching profession. This is as a result of a vivid nonchalant attitude exhibited by some of the Nigeria teachers. First, the effect of irregular payment of teachers’ salaries has cause an alarm for the performance of teachers in work. Again, the inadequate promotion of teachers has negative impact in discharging their duties effectively and efficiently, thus this leads to teachers’ low standard of living and sometimes abandons the teaching profession and they look for better paid job. The negligent of teachers’ welfare affect their service and it is cause by the attitude of all that are concern in the school as government the school administrators, school heads even the society at large who does not encourage teachers to put in their best. With these, the researchers adopt expository and descriptive method in carrying out this work. The authors recommend that school heads should make use of correct motivation strategies such as attitude motivation and recognition. Also autocratic/dictatorship leadership style should be discouraged. Again, society should respect and recognize teachers’ position in nation building equally communities should see the school as an institution that inculcate into individual society’s value and norms and see it a responsibility to donate its welfare.